SUSEPTIBILITAS MAGNETIK SISTEM PANASBUMI NON VULKANIK DESA TERAK MENGGUNAKAN METODE GEOMAGNETIK - Tri Kusmita; Yuant Tiandho; Yekti Widyaningrum; Umi Alawiyah (Jurnal Geosaintek, 2023)
Geothermal in Bangka Belitung islands are classified as radiogenic type of non-volcanic geothermal. Geothermal in this area was formed due to granite rocks that have been fractured, folded or faulted. Geothemal Terak has a surface temperature of 550C - 61.80C with a water discharge of 0.2 liters/second. This research aims to identify the forming rocks of geothermal system at Terak village based on magnetic field anomalies. Data acquisition was measured using a Proton Precession Magnetometer (PPM) along 2.5 km with 100 m spacing and 500 m spacing between lines. Data processing was analyzed using diurnal correction, IGRF correction, RTE (Reduce to the Equator) correction, anomaly separation using Upward Continuation. Modeling performed by applying 2D Inverse Modeling. The results indicated that the reservoir rock in Terak area with non-volcanic geothermal system was granite with susceptibility 42 x 103 - 49 x 103. The depth of the reservoir rock was partially at a depth of 30 - 125 meters above sea level and some were exposed on the surface (0 - 80 meters above sea level). Reservoir rocks are scattered in the northwest area of the study.